Activity Based Costing in Abouzar Health Center: A Case Study - Mostafa Rabieyan; Alireza Darrudi; Rajabali Darrudi; Ali Darrudi; Nader Bahman (Tehran University of Medical Sciences, 2017)
Background and Aim: Due to resource constraints and rising costs of health care, recognizing the costs exactly and controlling them are inevitable. Therefore, this study aimed to determine the cost of services rendered in Aboozar health center. Materials and Methods: This is a descriptive retrospective study and is based on the 2012 financial data. Data entry was done through EXCEL software and analyzed based on activity-based costing system in eight steps. Results: The results of this study are presented as a "unit cost" of 51 types of services offered in the final activity units of the health center studied. MMR vaccine injection by the vaccination unit with the unit cost of 31,919 Rials and visiting places of production and distribution by Environmental Health Unit with the unit cost of 298,475 Rials are respectively the lowest and highest unit costs of services rendered by the health center studied. Conclusion: Due to the high share of personnel costs of total expenditure (59%), increased labor productivity, improved access, and integrated units with similar services are also effective in reducing costs.